THE IMPACT OF AIR POLLUTION ON CARDIOVASCULAR PROBLEMS - Krismanuel, Hari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Introduction: Air pollution is a significant environmental issue with adverse effect on public health. Numerous studies have investigated the association between air pollution exposure and the development of cardiovascular diseases (CVD). The purpose of study: This literature review aims to provide an overview of recent studies, focusing on key findings, mechanisms, and potential interventions related to air pollution and CVD. Methods: A comprehensive search was conducted in Google Scholar, Web of Science and Pub Med for articles published between 2015 and 2024. The review prioritized epidemiological studies, experimental research, and previous review that examine the relationship between air pollution and cardiovascular conditions. Result study: Evidence showed that exposure to air pollution, particularly fine particulate matter (PM2.5) and gaseous pollutants, increased the risk of CVD, including heart risk, hypertension, stroke, and coronary artery disease. Mechanism involved endothelial dysfunction, inflammation and oxidative stress. Conclussion: To mitigate the global health risks associated with air pollution, improving air quality, implementing policy changes and promoting public health campaigns are essential.